This passing hour - Gould, Leslie, 1962- (Gould, Leslie. Amish memories, 2023)
"Mennonite Brenna Zimmerman's life grows complicated by her feelings for a Ukrainian soldier and her friendship with an Afghanistan War vet. But she's inspired by the story of her Amish great-great aunt's experience during World War II. How will Brenna find the courage to give up the comforts she craves for the life she truly wants?"--